Psychiatric symptoms and expression of glucocorticoid receptor gene in cocaine users: A longitudinal study. (February 2020) - Kluwe-Schiavon, B.; Schote, A.B.; Vonmoos, M.; Hulka, L.M.; Preller, K.H.; Meyer, J.; Baumgartner, M.R.; Grünblatt, E.; Quednow, B.B.
Abstract: Background: Chronic cocaine users (CU) display reduced peripheral expression of the glucocorticoid receptor gene ( NR3C1 ), which is potentially involved in stress-related psychiatric symptoms frequently occurring in CU. However, it is unknown whether psychiatric symptoms and lower NR3C1 expression are related to each other and whether reduction of drug consumption reverse them. Method: At baseline, NR3C1 mRNA expression was measured in 68 recreational CU, 30 dependent CU, and 68 stimulant-naïve controls. Additionally, the Revised Symptom Checklist (SCL-90R) and the Barratt Impulsiveness Scale (BIS) were assessed. At a one-year follow-up, the association between change in NR3C1 expression and psychiatric symptoms was examined in 48 stimulant-naïve controls, 19 CU who increased and 19 CU who decreased their consumption. At both test sessions, cocaine concentrations in hair samples were determined. Mixed-effects models were used to investigate how changes in drug use intensity affect severity of psychiatric symptoms and NR3C1 expression over time. Results: At baseline, recreational and dependent CU displayed elevated impulsivity and considerable symptom burden across most of the SCL-90R subscales. Time-group interaction effects were found for several impulsivity scores, SCL-90R Global Severity Index, Paranoid Thoughts, and Depression subscales as well as for NR3C1 expression. Pairwise comparisons showed that decreasing CU specifically improved in these SCL-90R subscales, while their NR3C1 expression was adapted. Finally, changes in NR3C1 expression were negatively correlated with changes in impulsivity but not SCL-90R scores. Conclusion: Our findings suggest that NR3C1 expression changes and some psychiatric symptoms are reversible upon reduction of cocaine intake, thus favouring abstinence-oriented treatment approaches.